Comments on “was hydrogen peroxide present before the arrival of oxygenic photosynthesis? The important role of iron(II) in the archean ocean” - Xiao Wu; Jianxi Zhu; Hongping He; Kurt O. Konhauser; Yiliang Li (Redox Biology, 2024)
Recent research has hypothesized that hydrogen peroxide (H2O2) may have emerged from abiotic geochemical processes during the Archean eon (4.0–2.5 Ga), stimulating the evolution of an enzymatic antioxidant system in early life. This eventually led to the evolution of cyanobacteria, and in turn, the accumulation of oxygen on Earth. In the latest issue of Redox Biology, Koppenol and Sies (vol. 29, no. 103012, 2024) argued against this hypothesis and suggested instead that early organisms would not have been exposed to H2O2 due to its short half-life in the ferruginous oceans of the Archean. We find these arguments to be factually incomplete because they do not consider that freshwater or some coastal marine environments during the Archean could indeed have led to H2O2 generation and accumulation. In these environments, abiotic oxidants could have interacted with early life, thus steering its evolutionary course.